Damless hydroelectric power plant - Zastola, Yevhen (My University, 2023)
The thesis explores the potential of using damless hydroelectric power plants as an effective and environmentally friendly solution to meet energy needs and reduce negative impact on the environment. It is determined that the implementation of such plants can provide sustainable development and address global environmental challenges. However, a thorough environmental impact assessment and cost calculation for the construction and maintenance of the plant are necessary before its implementation.
Keywords: damless hydroelectric power plant; renewable energy; sustainable development; environmental impact; cost calculation